Increasing Amino Acids Density Improves Broiler Live Weight - Nasr, J.; Kheiri, F. (International Journal of Poultry Science, 2011)
This research evaluates amino acid density in two phases throughout life in Arian male broilers to better understand the impact of increase and decrease dietary amino acids density in live weight performance. Four diets with different levels of amino acids density, High (H), Medium (M), Standard (S) and Low (L) were used in a completely randomized experimental design. All diets were isocaloric and isonitrogenous. Broilers fed H diet, body weight in 42 d was increased by 202 g compared with standard group (p<0.05). Levels of amino acids density had a significant effect on body weight in weeks 1, 2, 4, 5 and 6. Feeding broilers with H diet was significant highest in body weight in weeks 4, 5 and 6. H treatment was significant highest daily body weight gain from 22 to 42 (grower phase) and 1 to 42 day of age compared with S treatment (p<0.05). The results of this study suggest that high amino acids density throughout life optimized live weight and growth, whereas reductions in amino acids density reduced growth and live weight.